Pengaruh Kualitas Produk Dan Citra Merk Terhadap Sikap Serta Dampaknya Terhadap Loyalitas Pembelian Produk Sepatu Bata Di Toko Cabang Mall Paragon Semarang - Apriyani, Nova Cindy Ayu; Tjajahningsih, Endang (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze and describe the effect of product quality and brand image on consumer attitudes and the effect of consumer attitudes on product purchase loyalty at Bata Shoe Store Mall Paragon Semarang. This research is a type of descriptive quantitative research. This research is a type of descriptive quantitative research. The data collection technique in this study was a questionnaire which was prepared by reducing several aspects related to the research variables. The data collection tool in this study refers to the Likert Scale. Each statement item provides alternative answer choices prepared based on the Likert Scale with a range of five scales (1 to 5) which describe the level of conditions, namely certain categories that represent the respondent's answer choices. Research variables include independent variables consisting of product quality (X1) and brand image (X2), while the dependent variables in this study are consumer attitudes (Y1) and purchase loyalty (Y2). The data instrument test in this study uses validity and reliability tests. Model testing is done with the coefficient of determination test and the F test. Hypothesis testing uses a partial significance test or t test with the help of the SPSS application. The research findings are (1) Product quality has a significant effect on consumer attitudes (2) Brand image has a significant effect on consumer attitudes. (3) Consumer attitudes have a significant effect on loyalty.